Intermediate technology for increased food and feed production from deep black clay soils in the Ethiopian highlands - Jutzi, S.C.; Asamenew, G.; Tedla, A.; Astatke, A. (Food and Agriculture Organization of the United Nations, 1987)
Discusses intermediate technology for increased food and feed production from deep black clay soils (vertisols) in the Ethiopian highlands. Presents examples of improved soil/water/nutrient management on vertisols discussing tillage and animal powered surface drainage and its effect on crop yields and labour use, potentialities, and nutrient utilization and management. Also discusses briefly the relevance of low external input technologies for small holder subsistence farming, and crop-livestock interactions in vertisol management.